On ideology change and spatial and structural linkages between formal and informal economic sectors in Zimbabwean cities (1981-2010) - Gumbo, Trynos (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.